Efficacy of marbofloxacin for naturally occurring contagious caprine pleuropneumonia - Balikci, Engin; Kizil, Omer; Karapinar, Tolga; Karahan, Murat; Ozdemir, Haydar; Dabak, Murat (Elsevier, 2008)
The aim of the present study is to determine the efficacy of marbofloxacin used in goats with naturally occurring contagious caprine pleuropneumonia (CCPP). The study was performed in two groups (consisting of 15 animals in each group) with two different doses of 10% aqueous solution of marbofloxacin injected intramuscularly into the semitendinous muscle. 2 mg/kg BW for 3 days (total dose administered: 6 mg/kg BW) was injected to the first group (group 1) and 3 mg/kg for 2 times every other day (total dose administered: 6 mg/kg BW) was injected to the second group (group 2). Microbiological analyses revealed that the causative agent of the disease was Mycoplasma capricolum subsp. capripneumoniae. Cure rates for groups I and 2 were determined as 100% (15115 goats) and 93% (14/15 goats), respectively. The results of this field trial suggest that marbofloxacin could be an effective drug against CCPP in goats. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: goat; marbofloxacin; contagious caprine pleuropneumonia